Synthesis and Biocompatibility of Thermosensitive Poly(organophosphazene) Gels - 이배훈; 박정수; 송수창 (한국생체재료학회, 2003)
Thermosensitive poly(organophosphazenes) bearing PEG, hydrophobic amino acid esters (PheOEt, LeuOEt and IleOEt) and depsipeptide (GlyLacOEt) as side groups have been synthesized, and their biocompatibility was investigated. The present polymers were soluble in water at low temperature while their solutions form gels at body temperature. The polymer solutions (10 wt% aqueous solutions) were subcutaneously injected in rats and the intensity of the inflammatory response to the implants was monitored by histology. The polymer solutions form in situ gels after the subcutaneous injection and the gels had integrated for above 28 days. The present polymer gels showed a good biocompatibility, resulting in the minimum or mild foreign body reaction.